SU(3) lattice gauge theory with a mixed fundamental and adjoint plaquette action: lattice artefacts - Hasenbusch, Martin; Necco, Silvia (Journal of high energy physics, 2004)
We study the four-dimensional SU(3) gauge model with a fundamental and an adjoint plaquette term in the action. We investigate whether corrections to scaling can be reduced by using a negative value of the adjoint coupling. To this end, we have studied the finite temperature phase transition, the static potential and the mass of the 0++ glueball. In order to compute these quantities we have implemented variance reduced estimators that have been proposed recently. Corrections to scaling are analysed in dimensionless combinations such as Tc/(σ)1/2 and m0++/Tc. We find that indeed the lattice artefacts in e.g. m0++/Tc can be reduced considerably compared with the pure Wilson (fundamental) gauge action at the same lattice spacing.